2014
DOI: 10.1002/adsc.201400125
|View full text |Cite
|
Sign up to set email alerts
|

Bipyridine Periodic Mesoporous Organosilica: A Solid Ligand for the Iridium‐Catalyzed Borylation of CH Bonds

Abstract: With the goal to obtain a molecularly defined iridium(I) heterogeneous C À H functionalization catalyst, a periodic mesoporous organosilica (PMO) containing bipyridylene moieties in a matrix of biphenylene units as ligand platform was designed and fully characterized. The material exhibits a high surface area with small mesopores in a vermicular arrangement, and the pore walls show a highly crystal-like character. After surface passivation with chlorotrimethylsilane and functionalization with chloro(1,5-cycloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…Periodic mesoporous organosilica (PMO) form a new class of mesoporous materials which holds great promises for a wide variety of applications such as adsorption, catalysis, drug release studies in simulated biological media, chromatography, and enzyme immobilization . Since the pioneering independent works of Inagaki, Ozin, and Stein in 1999 who first described PMO materials, the size reduction of PMO to the nanoscale has been scarcely reported.…”
mentioning
confidence: 99%
“…Periodic mesoporous organosilica (PMO) form a new class of mesoporous materials which holds great promises for a wide variety of applications such as adsorption, catalysis, drug release studies in simulated biological media, chromatography, and enzyme immobilization . Since the pioneering independent works of Inagaki, Ozin, and Stein in 1999 who first described PMO materials, the size reduction of PMO to the nanoscale has been scarcely reported.…”
mentioning
confidence: 99%
“… 19 Moreover, Inagaki et al and Copéret et al reported an original solid, periodic mesoporous organosilicas (PMOs) with bipyridine ligands in the framework, as a unique platform for heterogeneous C–H borylation, which showed superior activity towards the homogeneous C–H borylation. 20 22 However, with continuous reuse of the catalysts, the reaction activity gradually decreased because of the collapse of the material structure, which was also observed in the water oxidation reaction by these PMOs. 23 Therefore, the development of novel stable scaffolds is still required for practical applications.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, molecular heterogeneous catalysts have attracted significant research interest for C–H activation using various solids as supports, such as polymer, 18 metal–organic frameworks (MOFs), 19 and silica-based materials. 11 , 20 22 For example, Lin et al synthesized UiO-type MOFs with 2,2′-bipyridine (bpy) as an orthogonal functional fragment to form solid catalysts for both borylation of C–H bonds and ortho -silylation of benzylic silyl ethers. 19 Moreover, Inagaki et al and Copéret et al reported an original solid, periodic mesoporous organosilicas (PMOs) with bipyridine ligands in the framework, as a unique platform for heterogeneous C–H borylation, which showed superior activity towards the homogeneous C–H borylation.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic Mesoporous Organosilicas (PMOs) is an alternative class of highly stable organosilica support materials with high surface area and organic functionalities uniformly distributed within the pores and the walls of the silica matrix. 14 16 Recent effort towards the immobilization of molecular complexes have shown that such materials constitute ideal platform towards robust molecularly-defined heterogeneous catalysts, 17 , 18 including for the photoreduction of CO 2 with Re- and Ru-based PMO materials. 19 , 20 …”
Section: Introductionmentioning
confidence: 99%